2017
DOI: 10.1523/jneurosci.2860-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Decoding of Spatial Attention and Working Memory from EEG Oscillations and Sustained Potentials

Abstract: In human scalp EEG recordings, both sustained potentials and alpha-band oscillations are present during the delay period of working memory tasks and may therefore reflect the representation of information in working memory. However, these signals may instead reflect support mechanisms rather than the actual contents of memory. In particular, alpha-band oscillations have been tightly tied to spatial attention and may not reflect location-independent memory representations per se. To determine how sustained and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
273
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(300 citation statements)
references
References 63 publications
24
273
3
Order By: Relevance
“…However, hemispheric asymmetries in alpha power were not modulated by the number of cued or non-cued items and were thus unrelated to the selection/inhibition of non-spatial information content (here: representation of different color values). This finding is in line with the notion that posterior alpha power is related to the spatial orienting of attention (Bae & Luck, 2018;Hakim, Adam, Gunseli, Awh, & Vogel, 2019). Importantly, we showed that withdrawing the focus of attention from the position of lateral working memory content involved an inhibitory attentional control process (see figure 3A and 3B).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, hemispheric asymmetries in alpha power were not modulated by the number of cued or non-cued items and were thus unrelated to the selection/inhibition of non-spatial information content (here: representation of different color values). This finding is in line with the notion that posterior alpha power is related to the spatial orienting of attention (Bae & Luck, 2018;Hakim, Adam, Gunseli, Awh, & Vogel, 2019). Importantly, we showed that withdrawing the focus of attention from the position of lateral working memory content involved an inhibitory attentional control process (see figure 3A and 3B).…”
Section: Discussionsupporting
confidence: 91%
“…Here, we assessed retinotopic modulations of posterior alpha power by focusing on posterior hemispheric asymmetries (see figure 3). As hypothesized, alpha power lateralization was insensitive to the number of cued or non-cued working memory items, in line with its role in the spatial orienting of attention (Bae & Luck, 2018;Hakim et al, 2019). While this insensitivity of posterior alpha power asymmetries to the number of cued vs. non-cued items was already indicated by an earlier investigation (Poch, Carretie, & Campo, 2017), we further corroborate the notion that the spatial orienting of the focus of attention in working memory is based on inhibition: As indicated in figure 3, hemispheric asymmetries in alpha power differed between conditions with lateral targets and lateral distractors.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This apparent discrepancy can be explained by assuming a flexible locus of distractor suppression, which either in case of only spatial regularities operates at the level of spatial priority maps, or in case of additional feature expectations operates at so‐called conspicuity maps coding specific feature dimensions . Given the tight link between alpha‐band activity and spatial attention, suppression operating at spatial priority maps likely relies on modulations of alpha oscillations. More work, however, is necessary to determine the functional significance of alpha‐band oscillatory activity, especially since recent work indicates that alpha oscillations may not signal top‐down inhibition of cortical activity per se, but stabilization of the current configuration of neuronal activity, possibly through enhancing signal‐to‐noise .…”
Section: Discussionmentioning
confidence: 99%
“…Together with representational similarity analysis, 2 MVPA has demonstrated promising capabilities in revealing subtle neural signature of cognitive processes in magnetoencephalography (MEG), electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) data. [3][4][5][6][7][8][9][10][11][12][13][14][15] In many neuroimaging studies, 4,[16][17][18] the pattern vector dimension (number of M/EEG channels or fMRI voxels) highly exceeds the number of data samples (experimental trials), thus incurring the "curse of dimensionality," 19,20 which consequently deteriorates the classifier performance.…”
Section: Introductionmentioning
confidence: 99%